Agathology of Multiplicity. Considerations Concerning the Indetermined Duality - Lavecchia, Salvatore (Peitho. Examina Antiqua, 2015)
This article intends to characterize the constructive function that the Indeterminate Duality may have played in Plato’s oral teaching. Far from being in itself – as some testimonia seem to suggest – the primary origin of evil, as origin of multiplicity the Indeterminate Duality can be perceived as intrinsically presupposed by Plato’s identification of the source of being with the supreme Good. The notion of good implicates for Plato namely an unconditioned impulse to relationality, which indicates that the supreme Good is to be considered as supreme origin not only of unity, but also of multiplicity (scil. non-unity) and alterity. In the absence of multiplicity and alterity, no real relation, and, therefore, no real manifestation of the Good could in fact take place. As a consequence (and in accord with the suggestions given by Simplicius), the Indeterminate Duality may be considered as source of that original differentiation as well as of that generativity without which the supreme Good would be discordant with its goodness.